Roma families and teachers: gaining visibility and recognition through the implementation of socio-educational policies - Silvia Carbone (University of Bologna, 2023)
One of the central issues of our age is early school leaving. In this paper it was decided to analyze to what extent early school leaving involves the Roma, one of the most marginalized social groups. The basic hypothesis, which has been advanced in close connection with the field research, is that the perception of the representations of Roma families and teachers can be mediated through an integrated planning, based on public-private partnership entrusted to the institutions and to the organizations present and active in the area, in order to guarantee the maintenance of individual and collective differences and by promoting mutual understanding. The aim of the research is to observe whether the effects of an integrated planning, where Roma are an active part, are useful for deconstructing that stereotype which feeds on cultural essentialities to justify marginalization and early school leaving. The EU in its 2019 report confirmed that more Roma children participate in early childhood and primary education (53% in 2016, compared to 47% in 2011). On the other hand, there are fewer premature abandonments (68% in 2016, and 87% in 2011). The research showed that integrated planning between Roma and the school community already represents an action of social integration, capable of enhancing and recognizing differences, while generating a decrease in dropouts and greater social inclusion.